2021
DOI: 10.1021/acsami.0c20624
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-Transcriptional Regulation of cFLIP for Effective Cancer Therapy Using pH-Ultrasensitive Nanoparticles

Abstract: Cellular FLIP (cFLIP) is a crucial player of apoptosis-regulated pathways that is frequently overexpressed in solid cancers. To inhibit c-FLIP, preand post-transcriptionally, a multifunctional nanoparticle (NP) was created to deliver cFLIP-specific small interfering RNA (siRNA) into cancer cells. Specifically, Vorinostat (Vor)-loaded mesoporous silica nanoparticles (MSN) were conjugated with polyethylenimine-biotin (PB), followed by electrostatically binding with cFLIP siRNA (Vor/siR@MSN-PB). To stabilize and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The acidic TME is an important feature of cancer [ 32 , 33 ]. Previous studies indicated that MnO 2 response to acidic TME leading to release of Mn 2+ according to chemical equation: MnO 2 + 2H + → Mn 2+ + H 2 O + 1/2O 2 ↑ [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The acidic TME is an important feature of cancer [ 32 , 33 ]. Previous studies indicated that MnO 2 response to acidic TME leading to release of Mn 2+ according to chemical equation: MnO 2 + 2H + → Mn 2+ + H 2 O + 1/2O 2 ↑ [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…After that, these samples were incubated with biotinylated universal secondary antibody and ABC reagents for 1 h at room temperature in a humidity chamber. The areas occupied by positive cells (%/mm 2 of tumor mass) and the mean numbers of positive cells (cells/mm 2 of tumor mass) were measured by a histological camera system and automated image analyzer as in the previous report 46 …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the silanol groups on the surface of MSNs could be modified by various organic functional groups through covalent bonds, such as NH 2 and COOH. 280 , 281 Wagner et al. 282 reported multifunctional nanocarriers (MSN–Ph in –avidin out ) based on core–shell MSNs.…”
Section: Backbones and Structures Of Multifunctional Nanoparticlesmentioning
confidence: 99%
“…Additionally, the silanol groups on the surface of MSNs could be modified by various organic functional groups through covalent bonds, such as NH 2 and COOH. 280,281 Wagner et al 282 reported multifunctional nanocarriers (MSN-Ph in -avidin out ) based on core-shell MSNs. The core of the MSNs was functionalized with phenyl to accommodate hydrophobic R848, and the outer surface was functionalized with carboxyl groups to allow continuous modification to attach a pHresponsive acetal linker and a biotin-avidin complex for enhancing anticancer effects with immune reaction.…”
Section: Nonmetallic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation